(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The stem bark of Holarrhena pubescence was tested for anti-diabetic, analgesic, anti-inflammatory and antidiarrheal activities. After 1, 4 and 12 weeks of treatment protocol in alloxan-induced diabetic rats, it showed very negligible reduction of blood glucose level. In 12 weeks treatment protocol H. pubescence demonstrated that, the extract at 300 and 600 mg/kg bw can reduce blood glucose level by 3 and 4 mmol/l, respectively. Bark extract possessed strong analgesic, anti-diarrheal and mild anti-inflammatory activities. A dose of 600-mg/kg showed 69.50% (p<0.05) of writhing inhibition compared to indomethacin (73.76%) for acetic acid-induced analgesic method. In formalin-induced anti-nociception, the extract at 300 and 600 mg/kg bw showed dose dependent antinociception (67.42% and 69.007%, respectively, p < 0.05). The anti-diarrheal study demonstrated significant antidiarrheal potential in a dose dependent manner as demonstrated by reduction of defecation by 64.92% and 71.43%, for 300- and 600-mg/kg bw, respectively. Dhaka Univ. J. Pharm. Sci. 17(1): 131-137, 2018 (June)